Mathematical modelling of the most effective goal of cholesterol-lowering treatment in primary prevention. Issue 5 (24th May 2022) - Soran, Handrean; Adam, Safwaan; Iqbal, Zohaib; Durrington, Paul
Abstract : Objective: To compare quantitatively different recommended goals for cholesterol-lowering treatment in the primary prevention of atherosclerotic cardiovascular disease (ASCVD). Design: Outcomes at pretreatment low-density lipoprotein (LDL) cholesterol concentrations from 2 to 5 mmol/L and 10-year ASCVD risk from 5% to 30% were modelled, using the decrease in risk ratio per mmol/L reduction in LDL cholesterol derived from randomised controlled trials (RCTs) of cholesterol-lowering medication. Data source: Summary statistics from 26 RCTs comparing treatment versus placebo or less versus more effective treatment and 12 RCTs in which statin was compared with a higher dose of the same statin or with a similar statin dose to which an adjunctive cholesterol-lowering drug was added. Setting: The different recommended goals are: (1) LDL cholesterol≤2.6 mmol/L (100 mg/dL); (2) LDL cholesterol≤1.8 mmol/L (70 mg/dL); (3) non-high density lipoprotein (HDL) cholesterol decrease of ≥40%; or (4) LDL cholesterol≤1.8 mmol/L (70 mg/dL) or decreased by ≥50% whichever is lower. Participants: RCT participants. Interventions: Statins alone or in combination with ezetimibe or proprotein convertase subtilisin/kexin type 9 inhibitors. Main outcome measures: For each of the recommended therapeutic goals, our primary outcome was the number of events prevented per 100 people treated for 10 years (N100 ) and the number of needed to treat (NNT) to prevent one event over 10 years. Results: At pretreatment LDL cholesterol 4–5 mmol/L, all four goals provided similar benefit with N100 1.47–16.45 (NNT 6–68), depending on ASCVD risk and pretreatment LDL cholesterol. With initial LDL cholesterol in the range 2–3 mmol/L, the target of 2.6 mmol/L was the least effective with N100 between 0 and 2.84 (NNT 35–infinity). The goal of 1.8 mmol/L was little better. However, reductions in non-HDL cholesterol by ≥40% or of LDL cholesterol to 1.8 mmol/L and/or by 50%, whichever is lower, were more effective, delivering N100 of between 0.9 and 9.33 (NNT 11–111). Percentage decreases in LDL cholesterol or non-HDL cholesterol concentration are more effective targets than absolute change in concentration in people with initial values of <4 mmol/L. Conclusions: The LDL cholesterol target of 1.8 mmol/L is most effective when initial LDL cholesterol is >4 mmol/L. The time has probably come for the LDL cholesterol goal of <2.6 mmol/L to be abandoned.